2003
DOI: 10.1002/mrm.10628
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of diffusion measurements using Cramer‐Rao lower bound theory and its application to articular cartilage

Abstract: A novel approach to optimized diffusion measurements by minimizing the Cramer-Rao lower bound (CRLB) with respect to the b-values used for diffusion measurement was investigated. The applicability of the CRLB to these measurements is shown by the close agreement between the CRLB prediction and the actual precision obtained from experimental results. Where studies using a propagation-of-errors approach have restricted the optimization of the diffusion measurement to two b-values and to specific diffusion coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 19 publications
2
85
0
1
Order By: Relevance
“…Previous studies revealed that larger numbers of unique diffusion directions are more beneficial for robust estimation of DTI and DKI parameters. [21][22][23][24][25] However, our results suggest that compared to a combination of b-values and NSA, the number of diffusion directions has a weaker influence on the accuracy of the MK maps. The number of diffusion directions can thus be compromised to some extent when scanning time is shortened.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies revealed that larger numbers of unique diffusion directions are more beneficial for robust estimation of DTI and DKI parameters. [21][22][23][24][25] However, our results suggest that compared to a combination of b-values and NSA, the number of diffusion directions has a weaker influence on the accuracy of the MK maps. The number of diffusion directions can thus be compromised to some extent when scanning time is shortened.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, they can be estimated without actually acquiring spectra, but purely based on a parameterized model function and the expected signal-to-noise ratio (SNR). This method of experiment optimization has been used in different fields (Anastasiou and Hall, 2004;Brihuega-Moreno et al, 2003;Ober et al, 2002) but only preliminary results of its use for in vivo MRS have been reported (Bolliger et al, 2012;Chong et al, 2007;Snyder and Lange, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the CRLB is not an estimate of the parameter variance directly, we can use it in a similar way to obtain good sampling configurations by minimizing it with respect to the sample points. In quantitative MRI, this method has been used to optimize sampling configurations for measuring T 2 relaxation time (22), diffusion coefficients (23), and the decomposition of water and fat signals in Dixon imaging (24). In a preliminary study Samson et al (25) used the CRLB to optimize MT acquisition.…”
mentioning
confidence: 99%